Предмет: Математика,
автор: zzzzz99999temirov
10 - 2·(3 – 4х) = 3·(6 + х)
Ответы
Автор ответа:
1
Ответ:
10+(-2)·(3-4х)=3·(6+х)
10-6+8х=18+3х
8х-3х=18-4
5х=14
х=2,8
Пошаговое объяснение:
Это легко
Автор ответа:
2
Пошаговое объяснение:
у меня так вышла
должно быть правильно
Приложения:
![](https://files.topotvet.com/i/e66/e661b48914da2ec515b654829314a25b.jpg)
Похожие вопросы
Предмет: Українська мова,
автор: andriyzvorskiy
Предмет: Другие предметы,
автор: ignanhitryak
Предмет: Английский язык,
автор: НККО6НГОА6АО
Предмет: Математика,
автор: MirasZhanna
Предмет: Физика,
автор: Аноним